A prospective cohort study of renal function and bone turnover in adults with hepatitis B virus (HBV)‐HIV co‐infection with high prevalence of tenofovir‐based antiretroviral therapy use. Issue 1 (16th May 2022) - Gizaw, Andinet; King, Wendy C.; Hinerman, Amanda S.; Chung, Raymond T.; Lisker‐Melman, Mauricio; Ghany, Marc G.; Khalili, Mandana; Jain, Mamta K.; Graham, Jacob; Swift‐Scanlan, Theresa; Kleiner, David E.; Sulkowski, Mark; et al.
Abstract: Objective: Tenofovir disoproxil fumarate (TDF) is a common component of antiretroviral therapy in hepatitis B virus (HBV)‐HIV co‐infected adults but few studies have evaluated worsening renal function and bone turnover, known effects of TDF. Methods: Adults from eight North American sites were enrolled in this cohort study. Research assessments were conducted at entry and every 24 weeks for ≤192 weeks. Bone markers were tested at baseline, week 96 and week 192 from stored serum. We evaluated changes in markers of renal function and bone turnover over time and potential contributing factors. Results: A total of 115 patients were prospectively followed; median age 49 years, 91% male and 52% non‐Hispanic Black. Duration of HIV was 20.5 years. TDF use ranged from 80% to 92% throughout follow‐up. Estimated glomerular filtration rate (eGFR) (ml/min/1.73m 2 ) decreased from 87.1 to 79.9 over 192 weeks ( p  < 0.001); however, the prevalence of eGFR <60 ml/min/1.73m 2 did not appear to differ over time (always <16%; p  = 0.43). From baseline to week 192, procollagen type I N‐terminal propeptide (P1NP) (146.7 to 130.5 ng/ml; p  = 0.001), osteocalcin (14.4 to 10.2 ng/ml; p  < 0.001) and C‐terminal telopeptides of type I collagen (CTX‐1) (373 to 273 pg/ml; p  < 0.001) decreased. Younger age, male sex and overweight/obesity versus normal weight predicted a decrease in eGRF. Black race, healthy weight versus underweight, advanced fibrosis, undetectable HBV DNA, and lower parathyroid hormone level predicted worsening bone turnover. Conclusion: In this HBV‐HIV cohort with high prevalence of TDF use, several biomarkers of renal function and bone turnover indicated worsening status over approximately 4 years, highlighting the importance of clinical awareness in co‐infected adults.